2011
DOI: 10.1007/s00423-011-0769-8
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal-hybrid vs. single-port-access vs. ‘conventional’ laparoscopic cholecystectomy: a prospective observational study

Abstract: Concerning the length of hospital stay, transvaginal-hybrid cholecystectomy and single-port cholecystectomy appear to be superior to 'conventional' laparoscopic cholecystectomy. Additionally, transvaginal-hybrid access is associated with significantly less pain in the early postoperative course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 22 publications
3
22
2
3
Order By: Relevance
“…Few studies reported of a benefit in hospital stay with SILC,[202425] we found no such benefit [Table 9]. …”
Section: Discussioncontrasting
confidence: 50%
“…Few studies reported of a benefit in hospital stay with SILC,[202425] we found no such benefit [Table 9]. …”
Section: Discussioncontrasting
confidence: 50%
“…36 Similar prospective studies have compared classic laparoscopic techniques to a hybrid TV cholecystectomy. 37 In each case, the findings of the aforementioned article by Zornig et al have been corroborated.…”
Section: Tv Accesssupporting
confidence: 59%
“…No major complications or conversions occurred and the mean operative time was 62.7 min (Table 1). Single-incision surgery using conventional laparoscopy has gained wide diffusion in various fields of abdominal surgery allowing to reduce surgical trauma and providing greater patient comfort [15][16][17]. However, it is still challenging due to the intrinsic impossibility of using a standard triangulation approach [18][19][20].…”
Section: Discussionmentioning
confidence: 99%